Housing and inequality The case of Luxembourg and its cross-border workers - Claveres, Guillaume (OECD Publishing, 2020)
The rate of homeownership is close to the OECD average in Luxembourg. However, strong house price increases, mainly driven by population growth and limited housing supply, led to a deterioration in affordability of housing, in particular for the young and added to the wealth gap between homeowners and renters
Keywords: Economics; Luxembourg